2020
DOI: 10.1017/s0004972720000180
|View full text |Cite
|
Sign up to set email alerts
|

On the Harmonic Zygmund Spaces

Abstract: In this paper we study a class ${\mathcal{Z}}_{H}$ of harmonic mappings on the open unit disk $\mathbb{D}$ in the complex plane that is an extension of the classical (analytic) Zygmund space. We extend to the elements of this class a characterisation that is valid in the analytic case. We also provide a similar result for a closed separable subspace of ${\mathcal{Z}}_{H}$ which we call the little harmonic Zygmund space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In [5], it is shown that the elements of the space Z H can be characterized in terms of the membership to the classical Zygmund class, and the corresponding norms are equivalent.…”
Section: Harmonic Zygmund Spacementioning
confidence: 99%
See 1 more Smart Citation
“…In [5], it is shown that the elements of the space Z H can be characterized in terms of the membership to the classical Zygmund class, and the corresponding norms are equivalent.…”
Section: Harmonic Zygmund Spacementioning
confidence: 99%
“…In [2], the first author pursued this study by extending several classes of Banach spaces, including the Bloch space B and its generalizations B α known as α-Bloch spaces introduced by Zhu in [3], the growth spaces A − α (where α > 0), the Zygmund space Z, and the analytic Besov spaces B p for p > 1. In particular, the linear structure and properties of the harmonic α-Bloch spaces B α H , the harmonic growth spaces A − α H (for α > 0), and the harmonic Zygmund space Z H were studied in [4,5]. e harmonic Besov spaces B p H for p > 1 were introduced in [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the Banach spaces of analytic functions on D have been gaining a great deal of attention, but for the harmonic extensions of analytic spaces, it is still limited. Besides [1] by F. Colonna, papers such as [2] for the study of the operator theory on some spaces of harmonic mappings, [3] for characterizations of Bloch-type spaces of harmonic mappings, [4] for composition operators on some Banach spaces of harmonic mappings, [5] for the study of harmonic Bloch and Besov spaces, [6] for the study harmonic Zygmund spaces, [7] for the study of harmonic ν-Bloch mappings and [8] for the study of harmonic Lipschitz-type spaces. For α > 0, α-Bloch space for harmonic mapping is defined such that…”
Section: Introductionmentioning
confidence: 99%
“…for characterization of Bloch type spaces of harmonic mapping, see [6], for harmonic zygmund spaces.…”
Section: Introductionmentioning
confidence: 99%